The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1177/00178969221139815
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sexuality education programme on young people’s STI/HIV knowledge, attitudes and risk behaviour in Northeast Nigeria

Abstract: Objective: The high prevalence of sexually transmitted infections (STIs) including human immunodeficiency virus (HIV) among Nigerian young people has been linked to poor knowledge, attitudes and risk behaviour. This study evaluated the effectiveness of a sexuality education programme (SEP) in improving adolescents’ STI/HIV knowledge and attitudes and reducing risk behaviour. Design: A quasi-experimental pre–post study was conducted. The experimental group ( n = 189) and comparison group ( n = 195) comprised se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The PRISMA flow chart (Figure 1) summarizes the search results showing 1021 results, 908 of which were non-duplicate citations, 720 studies excluded after title and abstract screening, full-text of 2 articles were not found and 180 studies excluded after full-text screening yielding 6 eligible studies. [14][15][16][17][18][19]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The PRISMA flow chart (Figure 1) summarizes the search results showing 1021 results, 908 of which were non-duplicate citations, 720 studies excluded after title and abstract screening, full-text of 2 articles were not found and 180 studies excluded after full-text screening yielding 6 eligible studies. [14][15][16][17][18][19]…”
Section: Resultsmentioning
confidence: 99%
“…Study locations include South-eastern Nigeria South-west South-south, Central, North-east and North-west. [14][15][16][17][18][19] Four studies adopted a quasi-experimental design with a control group except that conducted by Akuiyibo and his group. 13 While two studies were cross-sectional.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations